Laminated Glass

JP7629393B2Active Publication Date: 2025-02-13AGC INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021503522
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-04
Filing Date
2020-02-18
Publication Date
2025-02-13
Estimated Expiration
2040-02-18

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、調光フィルムを備える合わせガラスにおいて、調光フィルムの端部が保護された合わせガラスが、合わせガラスの外観を損なうことなくかつ生産性よく提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629393000001
    Figure 0007629393000001
  • Figure 0007629393000002
    Figure 0007629393000002
  • Figure 0007629393000003
    Figure 0007629393000003
Patent Text Reader

Abstract

The present invention provides laminated glass having: a pair of glass sheets facing each other; a pair of intermediate adhesive layers located between the pair of glass sheets so as to contact the pair of glass sheets in respective fashion; and a light control film, which is positioned between the pair of intermediate adhesive layers and in which the visible light transmittance can be switched, wherein the laminated glass is characterized in that: the laminated glass is substantially polygonal in plan view; on at least one side of the outer periphery part of the laminated glass, the outer periphery of the light control film is positioned a distance of w [mm] inwards from the outer periphery of the laminated glass in plan view; w, ti, and ts satisfy formula 1: 0 < w / ti < 7 / ts, where ts [mm] represents the thickness of the light control film, and ti [mm] represents the total thickness of the pair of intermediate adhesive layers; and the pair of intermediate adhesive layers are in contact with each other in the region from the outer periphery of the laminated glass to the outer periphery of the light control film.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to laminated glass, and more particularly to laminated glass provided with a light control film. [Background technology]

[0002] Smart glass is known as a type of window glass for vehicles, and has a light-control film sealed inside the laminated glass, allowing the transmittance to be electrically switched by turning a power switch on and off.

[0003] In smart glass, in order to protect the ends of the light-control film from the external environment, the light-control film is often cut to a size smaller than the glass plate or intermediate adhesive layer, and the ends are covered with the intermediate adhesive layer and enclosed in the laminated glass. Specifically, a frame-shaped intermediate adhesive layer is placed around the periphery of the light-control film, and this is sandwiched between two intermediate adhesive layers, which is then further sandwiched between a pair of glass plates (see, for example, Patent Document 1).

[0004] However, the use of a frame-shaped intermediate adhesive layer causes problems such as a decrease in workability in the lamination process and an increase in costs due to an increase in the amount of intermediate adhesive layer used.

[0005] In the existing technology, when a thin functional film, for example, an infrared reflective film, is enclosed in a laminated glass, it is common to encapsulate it without using a frame-shaped intermediate adhesive layer (see, for example, Patent Document 2). However, in the case of a light control film, a light control material is usually sandwiched between two plastic films, and it tends to be thicker than other functional films, and if a frame-shaped intermediate adhesive layer is not used, defects in appearance such as air remaining or bubbles will occur. As a result of intensive research, the present inventors have found that the above problem can be solved by controlling the thickness of the light control film and its positional relationship in the laminated glass. [Prior art documents] [Patent documents]

[0006]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0007] An object of the present invention is to provide a laminated glass provided with a dimming film, which can protect the end portion of the dimming film without impairing the appearance and has improved productivity.

Means for Solving the Problems

[0008] The laminated glass of the present invention a pair of glass plates facing each other, a pair of intermediate adhesive layers located between the pair of glass plates and each contacting the pair of glass plates, a laminated glass having a dimming film capable of switching the visible light transmittance located between the pair of intermediate adhesive layers, wherein the laminated glass is substantially polygonal in plan view, and at least one side of the outer peripheral portion of the laminated glass satisfies the following requirements (i-1) to (i-3). (i-1) The outer periphery of the dimming film is located inside by a distance w [mm] from the outer periphery of the laminated glass in plan view. (i-2) When the thickness of the dimming film is ts [mm] and the total thickness of the thicknesses of the pair of intermediate adhesive layers is ti [mm], the w, the ti, and the ts satisfy the following formula 1.

[0009] 0 < w / ti < 7 / ts Formula 1 (i-3) The pair of intermediate adhesive layers are in contact with each other in a region from the outer periphery of the laminated glass to the outer periphery of the dimming film.

Effects of the Invention

[0010] According to the present invention, in a laminated glass provided with a dimming film, the laminated glass with the end portion of the dimming film protected can be provided without impairing the appearance of the laminated glass and with high productivity.

Brief Description of the Drawings

[0011] [Figure 1] It is a front view of an example of an embodiment of the laminated glass of the present invention. [Diagram 2] It is a cross-sectional view taken along the line X-X of the laminated glass shown in FIG. 1. [Diagram 3] It is a table showing the evaluation results of Examples and Comparative Examples.

Embodiments for Carrying Out the Invention

[0012] Hereinafter, embodiments of the present invention will be described. Note that the present invention is not limited to these embodiments, and these embodiments can be changed or modified without departing from the spirit and scope of the present invention.

[0013] The laminated glass of the present invention is a laminated glass having a pair of glass plates facing each other, a pair of intermediate adhesive layers located between the pair of glass plates and each contacting the pair of glass plates, and a dimming film located between the pair of intermediate adhesive layers and having a switchable visible light transmittance, wherein the laminated glass is substantially polygonal in plan view, and at least one side of the outer peripheral portion of the laminated glass satisfies the following requirements (i-1) to (i-3). (i-1) The outer periphery of the dimming film is located inside by a distance w [mm] from the outer periphery of the laminated glass in plan view. (i-2) When the thickness of the dimming film is ts [mm] and the total thickness of the thicknesses of the pair of intermediate adhesive layers is ti [mm], the w, the ti, and the ts satisfy the following formula 1.

[0014] 0 < w / ti < 7 / ts Formula 1 (i-3) The pair of intermediate adhesive layers are in contact with each other in a region from the outer periphery of the laminated glass to the outer periphery of the dimming film.

[0015] In this specification, the edge means a ridge formed by joining two surfaces, and the periphery means an area having a certain width from the edge of a surface toward the center of the surface. In laminated glass, the edge means the outer periphery of the main surface of the laminated glass. The thickness of the laminated glass measured at the edge is the distance from the edge of one main surface of the laminated glass to the edge of the other main surface at the measurement position. The thickness of the laminated glass measured at the edge is also called the edge thickness of the laminated glass.

[0016] In the present invention, the outer periphery of the main surface of the laminated glass coincides with the outer periphery of the main surface of the glass sheets constituting the laminated glass. In this specification, the outer periphery side of the main surfaces of the laminated glass and the glass sheets when viewed from the center is referred to as the outer side, and the central side when viewed from the outer periphery is referred to as the inner side.

[0017] In this specification, "approximately the same shape and size" refers to having the same shape and size as seen by the human eye. For example, when two things are "approximately the same shape and size," it also includes a case where one has an outer peripheral shape without irregularities such as notches, and the other has an outer peripheral shape with fine notches or the like in part. In other cases, "approximately" has the same meaning as above. In this specification, "to" indicating a numerical range includes the upper and lower limit numerical values.

[0018] Hereinafter, an embodiment of the laminated glass of the present invention will be described with reference to the drawings. Fig. 1 is a front view of an example of an embodiment of the laminated glass of the present invention, and Fig. 2 is a cross-sectional view taken along line XX of the laminated glass shown in Fig. 1.

[0019] 1 and 2 includes a pair of glass plates 1A, 1B facing each other, and a pair of intermediate adhesive layers 2A, 2B in contact with the facing surfaces of the pair of glass plates 1A, 1B. In the laminated glass 10A, the pair of glass plates 1A, 1B and the pair of intermediate adhesive layers 2A, 2B are substantially quadrilateral in plan view, and have main surfaces of substantially the same shape and size.

[0020] The shape of the laminated glass of the embodiment in plan view is approximately polygonal. Approximately polygonal includes shapes in which the corners may have a radius of curvature of approximately 1000 mm or less. The number of corners of the polygon can be 3 to 8, and is appropriately selected depending on the application of the laminated glass. The shape of the laminated glass of the embodiment in plan view is preferably approximately quadrilateral.

[0021] The laminated glass 10A further includes a light control film 3 capable of switching visible light transmittance between the pair of intermediate adhesive layers 2A and 2B. The area of ​​the main surface of the light control film 3 is smaller than the area of ​​the main surfaces of the glass plates 1A and 1B, and the light control film 3 is disposed between the intermediate adhesive layers 2A and 2B such that the periphery of the main surface of the light control film 3 is located inside the periphery of the main surfaces of the glass plates 1A and 1B.

[0022] The outer periphery of the laminated glass 10A coincides with the outer periphery of the glass plates 1A and 1B. In the laminated glass 10A, the outer periphery of the light control film 3 is located a distance w [mm] inside the outer periphery of the laminated glass 10A in a planar view (satisfying requirement (i-1)). The opposing main surfaces of the intermediate adhesive layer 2A and the intermediate adhesive layer 2B are in contact with each other in a frame-shaped region from the outer periphery of the laminated glass 10A to the outer periphery of the light control film 3 (satisfying requirement (i-3)). In other words, in the laminated glass 10A, there is no frame layer consisting of the third intermediate adhesive layer on the outside of the light control film 3. The width of this region corresponds to the above-mentioned distance w.

[0023] In the laminated glass 10A, the thickness of the light control film 3 is denoted by ts [mm], the thicknesses of the intermediate adhesive layers 2A and 2B by ti1 [mm] and ti2 [mm], and the thicknesses of the glass plates 1A and 1B by tg1 [mm] and tg2 [mm]. The total thickness of the intermediate adhesive layers 2A and 2B is denoted by ti [mm].

[0024] The thickness of each component of the laminated glass is substantially constant in the plane, and the measurement position of the thickness is not particularly limited. However, as will be described later for the ends, the thickness of the intermediate adhesive layer may decrease depending on the manufacturing method. Therefore, the measurement position of the thickness of each component of the laminated glass shall be a position 50 mm or more inside from the end of the laminated glass. The thickness is measured by a normal method, for example, using calipers or a micrometer. Examples of the micrometer include Mitutoyo's Digimatic direct-advance micron micrometer 406-250 OMV25M.

[0025] For the laminated glass 10A, which is a laminated glass according to an embodiment of the present invention, w, ti, and ts satisfy the following formula 1 (satisfy requirement (i-2)).

[0026] 0 < w / ti < 7 / ts Formula 1 In the laminated glass of the embodiment, the relationship between w, ti, and ts preferably satisfies the following formula 2. However, in this case, ts is 0.25 mm or more. Hereinafter, this requirement is also referred to as requirement (i-4).

[0027] 0 < w / ti < 4.5 / ts Formula 2 In the laminated glass of the embodiment, it is sufficient to satisfy all of requirements (i-1) to (i-3) on at least one side of the outer peripheral portion. Preferably, the laminated glass of the embodiment satisfies all of requirements (i-1) to (i-3) on at least two sides of the outer peripheral portion, and more preferably satisfies all of requirements (i-1) to (i-3) on the entire periphery. In any case, it is more preferable to further satisfy requirement (i-4).

[0028] The laminated glass 10A shown in Figures 1 and 2 is an example that satisfies all of the requirements (i-1) to (i-3) around the entire periphery, and preferably satisfies the requirement (i-4). The w in such laminated glass 10A, which corresponds to the entire periphery of the laminated glass and the entire periphery of the light control film, satisfies formula 1, and preferably satisfies formula 2. As long as formula 1 is satisfied, and preferably within the range of formula 2, w may be different on each side of the periphery of the laminated glass 10A, and there may be a portion within one side where w is different. The above embodiment is also applicable to the case where the laminated glass is a polygon other than the approximately quadrilateral shown in Figure 1.

[0029] In the laminated glass of the embodiment, in at least one side, preferably all sides, that satisfies the requirements (i-1) to (i-3), w is preferably 100 mm or less, more preferably 50 mm or less, even more preferably 20 mm or less, and even more preferably 10 mm or less. When w is the above value or more, the area occupied by the light control film is large, the visible light transmittance over a wide area can be controlled, and the design is excellent. Furthermore, in the laminated glass of the embodiment, in at least one side, preferably all sides, that satisfies the requirements (i-1) to (i-3), w is preferably 1 mm or more, more preferably 3 mm or more, and particularly preferably 5 mm or more, from the viewpoint of protecting the end of the light control film.

[0030] For example, in the laminated glass 10A, if the total thickness ti of the intermediate adhesive layers 2A and 2B is 0.8 mm and the thickness ts of the light control film 3 is 0.35 mm, then w that satisfies formula 1 is less than 16.0 mm, and w that satisfies formula 2 is less than 11.4 mm.

[0031] The laminated glass of the embodiment satisfies the requirements (i-1) to (i-3), and preferably further satisfies the requirement (i-4), thereby protecting the edge of the light control film from the external environment and suppressing defects in appearance due to air remaining inside the laminated glass. This suppresses deterioration of the peripheral portion of the light control film when used for a long period of time, resulting in a highly reliable laminated glass. Furthermore, since no frame-shaped intermediate adhesive layer is used, the workability is good and it is economical, so the productivity is good.

[0032] Here, as shown in Figures 1 and 2, when the thickness of the laminated glass 10A measured at the end of the laminated glass 10A indicated by measurement point E in Figure 1 is T1, and the thickness of the laminated glass 10A measured at a position 50 mm inside from the end indicated by measurement point E (measurement point I in Figure 1) is T2, it is preferable that T2-T1 is 0.28 mm or less. When T2-T1 is in the above range, residual stress inside the laminated glass is small, and defects such as peeling and foaming are unlikely to occur. T2-T1 is more preferably 0.2 mm or less, and even more preferably 0.15 mm or less.

[0033] The thicknesses T1 and T2 are measured by a conventional method, for example, by using a vernier caliper or a micrometer, such as Mitutoyo's Digimatic Linear Micrometer 406-250 OMV25M.

[0034] The phenomenon of the thickness of the laminated glass becoming smaller at the edge is caused by the fact that, as described below, during the manufacturing process of the laminated glass 10A, a process of degassing the periphery of the laminate of the glass plates 1A and 1B, the intermediate adhesive layers 2A and 2B, and the light control film 3, and of heating and pressing the laminate, which results in a large compressive force being applied to the edge of the laminate. For this reason, in the obtained laminated glass 10A, a force acts in the direction in which the edge spreads (in the direction shown by the arrow in FIG. 2) due to the restoring force of the glass plates 1A and 1B so that the thickness becomes the same as the thickness of the inside, and the thickness increases from the time of manufacturing. For the purpose of explanation, FIG. 2 shows the characteristics of the actual product in an exaggerated manner.

[0035] The thickness of the laminated glass obtained through the above-mentioned manufacturing process is generally uniformly smaller at the edge than at the inside over the entire circumference of the laminated glass. Therefore, in the laminated glass of the embodiment of the present invention, the thickness may be measured at least at two points, an arbitrary point at the edge (measurement point E in the laminated glass 10A) and a position 50 mm inward from the edge (measurement point I in the laminated glass 10A), as exemplified in the laminated glass 10A. The arbitrary point at the edge may be any point on the circumference of the laminated glass.

[0036] In addition, the position 50 mm inward from the measurement point of the edge thickness is, for example, a position 50 mm inward from the measurement point on a line perpendicular to the measurement point on one straight side of the periphery of the laminated glass. In the case where the measurement point is on a straight side of the periphery of the laminated glass, it is a position 50 mm inward from the measurement point on the line perpendicular to the measurement point on the side. In the case where the periphery is curved, it is a position 50 mm inward from the measurement point on the perpendicular line to the tangent to the measurement point. In FIG. 1, a position 50 mm inward from the periphery of the laminated glass 10A is indicated by a frame line M. In the laminated glass 10A, when an arbitrary point on the periphery is set as the measurement point E of the edge thickness, a point on the frame line M where the above relationship holds with respect to the measurement point E is set as the measurement point I 50 mm inward from the edge.

[0037] Hereinafter, each element constituting the laminated glass 10A will be described. [Glass plate] The glass plates 1A and 1B used in the laminated glass 10A according to the embodiment of the present invention may be made of transparent inorganic glass or organic glass (resin). As the inorganic glass, ordinary soda-lime glass (also called soda-lime silicate glass), borosilicate glass, alkali-free glass, quartz glass, etc. may be used without any particular limitation. Among these, soda-lime glass is particularly preferred. There is no particular limitation on the forming method, but for example, float plate glass formed by the float method or the like is preferred. In the case of inorganic glass, the glass may have a surface stress due to a strengthening treatment such as physical strengthening or chemical strengthening.

[0038] Examples of organic glass (resin) include polycarbonate resin, polystyrene resin, aromatic polyester resin, acrylic resin, polyester resin, polyarylate resin, polycondensation product of halogenated bisphenol A and ethylene glycol, acrylic urethane resin, halogenated aryl group-containing acrylic resin, etc. Among these, polycarbonate resin such as aromatic polycarbonate resin and acrylic resin such as polymethyl methacrylate acrylic resin are preferred, and polycarbonate resin is more preferred. Furthermore, among polycarbonate resins, bisphenol A polycarbonate resin is particularly preferred. The glass plate may be composed of two or more of the above-mentioned resins.

[0039] The glass may be a colorless transparent material to which no coloring component is added, or a colored transparent material that is colored within a range that does not impair the effects of the present invention. Furthermore, one type of glass or a combination of two or more types of glass may be used, for example, a laminated substrate having two or more layers. Although it depends on the application location of the laminated glass, inorganic glass is preferable as the glass.

[0040] The pair of glass sheets 1A and 1B used in the laminated glass 10A may be made of different materials. When the laminated glass 10A is installed in a vehicle or building, it is preferable that the glass sheet located on the vehicle interior side or the interior side is soda-lime glass, and contains 0.4 mass% or more of iron in the composition as the total iron amount based on oxide, calculated as Fe2O3. When the iron content of the glass sheet on the vehicle interior side or the interior side is within the above range, the haze of the light control film is high, and even if the haze is 5% or more, for example, the haze is difficult to see from the vehicle interior side or the interior side, which is preferable.

[0041] The thicknesses tg1 and tg2 of the glass plates 1A and 1B can be appropriately selected depending on the application location of the laminated glass 10A, but generally, each is preferably independently 0.2 to 5 mm. From the viewpoint of achieving both weight reduction and rigidity of the laminated glass, 0.5 to 5 mm is more preferable, 1.1 to 3.5 mm is further preferable, and 1.6 to 3.0 mm is particularly preferable. The glass plates 1A and 1B may have a three-dimensional curvature from the viewpoint of the design or functionality of the installation location.

[0042] The plate thicknesses tg1 and tg2 of the pair of glass plates 1A and 1B may be the same or different. When the plate thicknesses of the glass plates 1A and 1B are different, it is preferable that the plate thickness of the glass plate located on the inside when the laminated glass 10A is installed in a window or the like, for example, the plate thickness of the glass plate located on the inside of the car in the case of an automobile window glass, or the plate thickness of the glass plate located on the outside in the case of a building window glass, is smaller than the plate thickness of the glass plate located on the outside. When the plate thicknesses of the glass plates are in the above relationship, heat generated from the light control film or heat caused by sunlight is easily released to the inside of the car or the inside of the building, so that deterioration of the light control film due to heat can be suppressed.

[0043] Furthermore, the glass plates 1A and 1B may be coated on their surfaces exposed to the atmosphere with a coating that provides water repellency, hydrophilicity, antifogging, low radiation, ultraviolet absorption, etc. The opposing surfaces of the glass plates 1A and 1B may be coated with a functional coating such as an infrared shielding coating or a conductive coating. Providing a low reflection film on the vehicle interior or interior side of the laminated glass 10A is preferable because it can prevent reflections on the glass surface, particularly at night, and provides a good design.

[0044] When the opposing surfaces of the glass plates 1A, 1B have the above-mentioned functional coating, the intermediate adhesive layers 2A, 2B described below are configured to contact the functional coating on the opposing surfaces of the glass plates 1A, 1B. [Intermediate adhesive layer] The pair of intermediate adhesive layers 2A, 2B in the laminated glass 10A have main surfaces of approximately the same shape and size as the main surfaces of the glass plates 1A, 1B. The intermediate adhesive layers 2A, 2B are provided so as to contact the opposing surfaces of the glass plates 1A, 1B, respectively, while sandwiching the light control film 3. In this way, the intermediate adhesive layers 2A, 2B have the function of bonding the light control film 3 between the pair of glass plates 1A, 1B so as to sandwich it between them via the intermediate adhesive layers 2A, 2B, and integrating them into the laminated glass 10A.

[0045] Here, specific examples of intermediate adhesive layers 2A and 2B include compositions containing the following thermoplastic resins as their main components, which are formed into sheets having main surfaces of approximately the same shape and dimensions as the main surfaces of glass plates 1A and 1B.

[0046] The thermoplastic resin is not particularly limited as long as it can be integrated when a composition containing the thermoplastic resin as a main component is formed into a sheet-like film as a pair of intermediate adhesive layers 2A, 2B, sandwiching the light control film 3 and inserting it between a pair of glass plates 1A, 1B, and heating and pressing it to form a laminated glass 10A. Although the optical performance required varies depending on the properties of the light control film to be enclosed in the laminated glass, it is preferable that the intermediate adhesive layer has a visible light transmittance of 80% or more when combined with only ordinary colorless and transparent glass to form a laminated glass.

[0047] Specific examples of the thermoplastic resin include polyvinyl acetal resins such as polyvinyl butyral resin (PVB), polyvinyl chloride resins, saturated polyester resins, polyurethane resins, ethylene-vinyl acetate copolymer resins (EVA), ethylene-ethyl acrylate copolymer resins, ionomer resins, and cycloolefin polymers (COP), which have been used conventionally as intermediate adhesive layers. Among these, PVB, EVA, polyurethane resins, ionomer resins, and COP are preferred. These thermoplastic resins may be used alone or in combination of two or more.

[0048] The thermoplastic resin for the intermediate adhesive layer of the laminated glass is selected in consideration of the balance of various properties such as transparency, weather resistance, strength, adhesive strength, penetration resistance, impact energy absorption, moisture resistance, heat insulation, and sound insulation, depending on the application. From the viewpoint of these conditions, among the above-mentioned thermoplastic resins, a resin composition in which the vinyl acetate unit in an ethylene-vinyl acetate copolymer is saponified, and an ethylene-vinyl acetate copolymer resin composition characterized by containing an organo-layered clay, a silane coupling agent, etc. in an ethylene-vinyl acetate copolymer as described in Japanese Patent No. 5625781 are preferable. By containing an organo-layered clay, the moisture permeability can be significantly reduced compared to a normal ethylene-vinyl acetate copolymer resin composition. In addition, a resin composition containing a modified block copolymer hydrogenated product described in Japanese Patent Publication No. 2015-821 can also be preferably used.

[0049] The intermediate adhesive layer has a minimum storage modulus of 2.0 x 10 in the temperature range of 90 to 120 °C when dynamic viscoelasticity is measured at a measurement frequency of 10 Hz. 6 Pa or less (hereinafter referred to as requirement (ii-1)). When the intermediate adhesive layer satisfies requirement (ii-1), it has a predetermined flexibility in the temperature range where heat-pressure bonding is performed. As a result, a pair of intermediate adhesive layers have shape-following properties from the area where they contact the peripheral portion of the light control film to the area where they contact each other, that is, over the frame-shaped area of ​​width w from the outer periphery of the laminated glass to the outer periphery of the light control film, facilitating sufficient bonding without leaving air.

[0050] The minimum storage modulus of the intermediate adhesive layer is 8.0×10 5 Pa or less is more preferable, and 5.0×10 5 From the viewpoint of ensuring a predetermined rigidity in the temperature range in which thermocompression is performed, the storage modulus of the intermediate adhesive layer is preferably 2.0×10 Pa or less. 5 It is preferable that the pressure is 1 Pa or more.

[0051] In order to adjust the storage modulus of the intermediate adhesive layer, for example, the unit amount of vinyl acetate in the thermoplastic resin constituting the intermediate adhesive layer can be increased to lower the storage modulus of EVA, while the storage modulus of PVB can be lowered by adjusting the composition to increase the amount of plasticizer.

[0052] As for ionomer resins, for example, in ionomer resins in which a copolymer of ethylene and (meth)acrylic acid, a (meth)acrylic acid ester, or the like is crosslinked with a metal ion, the storage modulus can be reduced by increasing the ratio of (meth)acrylic acid or (meth)acrylic acid ester to ethylene.

[0053] In the case of COP, for example, a resin composition containing a modified hydrogenated block copolymer [3] obtained by introducing an alkoxysilyl group into a hydrogenated block copolymer [2] obtained by hydrogenating 90% or more of all unsaturated bonds of a block copolymer [1] having at least two polymer blocks [A] mainly composed of repeating units derived from an aromatic vinyl compound and at least one polymer block [B] mainly composed of repeating units derived from a chain-like conjugated diene compound, the ratio of wA to wB being 30:70 to 60:40, where wA is the weight fraction of all polymer blocks [A] in the entire block copolymer and wB is the weight fraction of all polymer blocks [B] in the entire block copolymer. The storage modulus can be reduced by lowering the ratio of wA.

[0054] In this manner, by adjusting the storage modulus of the thermoplastic resin constituting the intermediate adhesive layer, an intermediate adhesive layer that satisfies the requirement (1) can be obtained.

[0055] For the intermediate adhesive layer, a material that does not affect the function of the light control film during production and use is preferable. Therefore, the thermoplastic resin should not contain a plasticizer, or, in the case of a thermoplastic resin that contains a plasticizer, the thermoplastic resin should contain a plasticizer that does not affect the light control film.

[0056] Furthermore, the heating temperature during the formation of the laminated glass is set according to the thermoplastic resin for the intermediate adhesive layer, but if the heating temperature is equal to or higher than the heat resistance temperature of the light control film, the light control film may not function sufficiently when the laminated glass is formed. From this point of view, it is preferable to select a thermoplastic resin for the intermediate adhesive layer so that the forming temperature of the laminated glass is equal to or lower than the heat resistance temperature of the light control film used.

[0057] As described above, a thermoplastic resin-containing composition containing the above thermoplastic resin as a main component is used to prepare the intermediate adhesive layers 2A and 2B. The thermoplastic resin-containing composition may contain one or more of various additives such as infrared absorbers, ultraviolet absorbers, fluorescent agents, adhesion regulators, coupling agents, surfactants, antioxidants, heat stabilizers, light stabilizers, dehydrating agents, antifoaming agents, antistatic agents, and flame retardants, depending on various purposes, as long as the effects of the present invention are not impaired. These additives are uniformly contained throughout the intermediate adhesive layers 2A and 2B.

[0058] The thicknesses ti1 and ti2 of the intermediate adhesive layers 2A and 2B may satisfy the formula 1 in terms of the relationship between the total thickness ti and w and ts. Specifically, similar to the intermediate adhesive layers usually used for laminated glass, the thickness per layer is preferably 0.3 to 0.8 mm, and the total thickness of the two layers is preferably 0.6 to 1.6 mm. If the thicknesses ti1 and ti2 per layer of the intermediate adhesive layer are each less than 0.3 mm, or the total thickness ti of the two layers is less than 0.6 mm, the strength may be insufficient, and peeling may occur easily if the glass mismatch is large. If the total thickness ti of the intermediate adhesive layers 2A and 2B exceeds 1.6 mm, the weight becomes large, which may cause problems when assembled to a vehicle.

[0059] The thicknesses ti1 and ti2 of the intermediate adhesive layers 2A and 2B may be the same or different. When the thicknesses of the intermediate adhesive layers 2A and 2B are different, it is preferable that the thickness of the intermediate adhesive layer located on the inner side of the glass plate when the laminated glass 10A is installed in a window, for example, the thickness of the intermediate adhesive layer located on the inner side of the car window glass or the indoor side of a building window glass, is smaller than the thickness of the intermediate adhesive layer located on the outer side. When the thicknesses of the intermediate adhesive layers are in the above relationship, heat generated from the light control film or heat caused by sunlight is easily released to the inner side of the car or indoor side, so that deterioration of the light control film due to heat can be suppressed.

[0060] The intermediate adhesive layers 2A and 2B are not limited to a single-layer structure. The intermediate adhesive layers 2A and 2B may be the same, but are not necessarily the same, and can be independently selected to have a single-layer structure or a multi-layer structure.

[0061] Incidentally, when the intermediate adhesive layer is prepared as an adhesive film or the like during the manufacture of laminated glass, it is preferable that the intermediate adhesive layer has an embossment. Usually, the material film that becomes the intermediate adhesive layer of laminated glass has an embossment, and when the material film is sandwiched between glass plates to form a laminate and then heat-pressed, the embossment functions as an air passage, and heat-pressed bonding is performed while the air between the layers of the laminate is sufficiently exhausted, and finally the embossment in the material film disappears to form an intermediate adhesive layer, and a high-quality laminated glass without residual air bubbles is obtained. [Light control film] As the light control film 3, light control films used in smart glass and the like, having a thickness ts of 0.1 mm to 1 mm, preferably 0.1 mm to 0.7 mm, more preferably 0.1 mm to 0.4 mm, can be used. In general, if the thickness is less than 0.1 mm, it is difficult to handle when preparing laminated glass, and if it is more than 1 mm, the rigidity of the substrate increases and it becomes difficult to follow the curved surface. If ts is within this range, the range of w can be set to a preferred range so as to satisfy formula 1 or formula 2 within the above range of ti.

[0062] Here, in the laminated glass of the embodiment, it is preferable from the viewpoint of design that the ratio of the area of ​​the light control film to the area of ​​the laminated glass in a plan view is 0.7 or more. If it is less than 0.7, the frame-shaped area becomes too wide, which may impair the appearance.

[0063] As the light control film 3, for example, a suspended particle device (SPD) film can be used. As the SPD film, a general SPD film can be used, which is configured by sandwiching a polymer layer containing suspended particles that can be oriented by application of a voltage between two electrically insulating films coated with a transparent conductive film on the inside. With such an SPD film, when the power switch is turned on and a voltage is applied between the transparent conductive films, the suspended particles in the polymer layer are oriented, resulting in a state of high visible light transmittance and high transparency. When the power switch is turned off, the suspended particles in the polymer layer are not oriented, resulting in a state of low visible light transmittance and low transparency.

[0064] As the SPD film, for example, a commercially available product such as LCF-1103DHA (product name, manufactured by Hitachi Chemical Co., Ltd.) can be used. Such commercially available products are supplied in a predetermined size, and can be cut to the desired size before use. The thickness of the SPD film used in the laminated glass is preferably within the range of the thickness ts of the light control film described above, and is preferably 0.2 to 0.4 mm from the viewpoints of ease of handling and availability.

[0065] By using the SPD film, the visible light transmittance can be electrically switched between high and low states. When the visible light transmittance of the SPD film is low, the contrast ratio between the HUD image and the background can be improved by projecting the HUD image onto the HUD display area where the SPD film is present.

[0066] In addition, the contrast ratio between the HUD image and the background can also be improved when a polymer dispersed liquid crystal (PDLC) is used as the light control film 3 instead of the SPD film. The PDLC film can be made by mixing a prepolymer, a nematic liquid crystal, and a spacer material in a specific ratio, and then placed between two soft transparent conductive films. The working principle includes the following: When no electric field is applied, the liquid crystal droplets can be randomly distributed in the polymer material with their directors freely oriented.

[0067] In such cases, the refractive index of the liquid crystal for normal light does not match that of the polymer material, causing a relatively strong scattering effect on the light, resulting in a translucent or opaque "milky" appearance of the PDLC film. Under an electric field, the liquid crystal droplets can align their directors along the direction of the external electric field due to their positive dielectric anisotropy properties. When the refractive index of the liquid crystal for normal light matches that of the polymer material, the light can pass through the PDLC film, and the PDLC film will therefore have a transparent appearance. Specifically, the higher the voltage supplied to the PDLC film, the more transparent the PDLC film will be.

[0068] As the PDLC film, for example, a commercially available product such as MIYO film (manufactured by Kyushu Nanotec Optics Co., Ltd.) can be used. Note that such commercially available products are supplied in a predetermined size, and are cut to the desired size before use. Note that the thickness of the PDLC film used in the laminated glass is preferably within the range of the thickness ts of the light control film described above, and is preferably 0.1 to 0.4 mm from the viewpoints of ease of handling and availability.

[0069] In addition, the contrast ratio between the HUD image and the background can be improved when any of the following light control films is used as the light control film 3: polymer network liquid crystal (PNLC), guest-host liquid crystal, VA (Vertical Alignment) type liquid crystal, TN (Twisted Nematic) type liquid crystal, photochromic, electrochromic, or electrokinetic. In addition to the above-mentioned components, the laminated glass of the embodiment may optionally include other layers as long as the effects of the present invention are not impaired. (Other layers) In the laminated glass, a dark-colored concealing layer may be provided in a strip shape on a part or all of the peripheral edge of the main surface of at least one of the pair of glass sheets constituting the laminated glass, the main surface being in contact with the intermediate adhesive layer, for the purpose of concealing the attachment portion to a frame or the like, wiring conductors, etc. In the laminated glass of the embodiment, such a dark-colored concealing layer may be provided as another layer.

[0070] An example of a dark-colored concealing layer is a black ceramic layer. The black ceramic layer can be formed using a known material such as a colored ceramic paste. For example, an ink formed by dispersing a dark-colored pigment, glass frit, a refractory filler, and a resin such as ethyl cellulose in a solvent is used as the ink used to form the black ceramic layer. Usually, the ink is printed in a predetermined pattern on a glass plate, and the ink is pre-baked by drying or ultraviolet irradiation, and then fired at a high temperature to obtain a black ceramic layer completely baked on the glass plate. In addition, an intermediate adhesive layer having a dark-colored pigment, a colored film in which a resin film is printed in a dark color, and the like can also be used to form a dark-colored concealing layer.

[0071] From the viewpoint of design, the width of the dark-colored concealing layer of the laminated glass may be narrowed or the dark-colored concealing layer may not be provided. An example of the laminated glass that does not have a dark-colored concealing layer is a door glass for a vehicle.

[0072] In the laminated glass, when the width of the dark-colored concealing layer is narrowed or no dark-colored concealing layer is provided at the periphery, the laminated glass of the present invention satisfies the requirements (i-1) to (i-3), and the distance w between the outer periphery of the light control film and the outer periphery of the laminated glass can be reduced without impairing the appearance of the laminated glass and while ensuring the durability of the light control film, which is preferable. When the width of the dark-colored concealing layer is narrowed, specifically, when the width is 100 mm or less, further 50 mm or less, and particularly 20 mm or less, the effect of the present invention can be particularly notably enjoyed. Within the scope of the present invention, the w of the short side may be relatively small compared to the long side of the polygon in plan view from the viewpoint of design. In this way, the width of the concealing layer on the short side can be reduced. [Laminated glass manufacturing] The laminated glass according to the embodiment of the present invention can be manufactured by a commonly used known technique. For example, in the laminated glass 10A, a laminate is prepared in which a light control film 3 is arranged between a pair of intermediate adhesive layers 2A and 2B so as to have a predetermined positional relationship, and this is inserted between a pair of glass plates 1A and 1B to prepare a laminated glass precursor, which is a laminated glass before pressure bonding in which the glass plate 1A, intermediate adhesive layer 2A, light control film 3, intermediate adhesive layer 2B, and glass plate 1B are laminated in this order. When other layers are included, the laminated glass precursor is prepared by laminating the glass plate and each layer in the same lamination order as the laminated glass obtained.

[0073] This laminated glass precursor is placed in a vacuum bag such as a rubber bag, and this vacuum bag is connected to an exhaust system. The laminated glass of the embodiment can be obtained by bonding the precursor at a temperature of about 70 to 110°C while vacuum suction (degassing) so that the pressure inside the vacuum bag is reduced to a reduced pressure of about -65 to -100 kPa (hereinafter also referred to as "vacuum heat and pressure bonding"). Furthermore, a pressure bonding process in which heating and pressurization are performed under conditions of 100 to 110°C and a pressure of 0.6 to 1.3 MPa (hereinafter also referred to as "pressure heat and pressure bonding") can be performed to obtain a laminated glass with even greater durability.

[0074] Pressure-heat-compression bonding is typically performed using an autoclave. By performing pressure-heat-compression bonding after vacuum-heat-compression bonding, it is possible to alleviate the reduction in thickness of the edge of the laminated glass obtained by vacuum-heat-compression bonding, which is caused by the thickness of the light-control film being small by the thickness ts of the light-control film in the frame-like region of width w where the light-control film of the laminate is not present. Specifically, the above T2-T1 can be easily set to 0.28 mm or less, more preferably 0.2 mm or less, and even more preferably 0.15 mm or less. This can eliminate residual stress in the laminated glass and suppress the occurrence of defects such as peeling and foaming of the intermediate adhesive layer.

[0075] In the present invention, in a laminated glass provided with a light control film, it is possible to protect the edge of the light control film without impairing the appearance, and a laminated glass with improved productivity can be obtained. The laminated glass of the present invention is suitably used, for example, as a window glass for a vehicle. EXAMPLES

[0076] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the embodiments and examples described below. Examples 1 to 6, 9 to 22, and 25 to 42 are examples, and Examples 7, 8, 23, and 24 are comparative examples. [Examples 1 and 2] (Making laminated glass) 1 and 2 was produced as follows. Hereinafter, the components of the evaluation sample corresponding to the components of the laminated glass 10A will be described with the same reference numerals as those in the laminated glass 10A.

[0077] Two soda lime glass glass plates 1A and 1B (manufactured by AGC, commonly known as FL, 2 mm thick, 150 mm x 150 mm square), two saponified EVA intermediate adhesive layers 2A and 2B (manufactured by Tosoh-Nikkemi, Mersen G (trade name), 0.4 mm thick, 150 mm x 150 mm square), and one light control film 3 (manufactured by Hitachi Chemical, LCF-1103DHA90 (trade name), SPD light control film, 0.35 mm thick, 140 mm x 140 mm square) were prepared. These were laminated in the order of one glass plate 1A, one EVA intermediate adhesive layer 2A, SPD light control film 3, the other EVA intermediate adhesive layer 2B, and the other glass plate 1B to obtain a laminate. The distance w between the periphery of the SPD light control film 3 and the periphery of the laminate was 5 mm on all four sides.

[0078] The laminate obtained above was placed in a rubber vacuum pack and degassed (vacuum pressure: -90 kPa), then placed in an oven maintained at 100°C, left for 60 minutes, vacuum-heated and pressed, and then removed from the rubber vacuum pack to obtain laminated glass 1A. The laminated glass 1A was pressurized and heated and pressed in an autoclave at 110°C and a pressure of 1.3 MPa for 20 minutes to obtain laminated glass 1B. In the laminated glass 1A and the laminated glass 1B, the thickness ts of the SPD light control film 3, the total thickness ti of the intermediate adhesive layers 2A and 2B, and the distance w between the outer periphery of the SPD light control film 3 and the outer periphery of the laminated glass are all the same as the values ​​of the laminated glass described above. The laminated glass 1A was taken as Example 1, and the laminated glass 1B was taken as Example 2.

[0079] For the laminated glass 1A and the laminated glass 1B, the thickness T1 at one point (measurement point E) at the end and the thickness T2 at a position (measurement point I) 50 mm inward from the one point at the end (measurement point E) were measured with a vernier caliper, and the thickness difference = thickness T2 [mm] at a position (measurement point I) 50 mm inward from the end of the laminated glass - thickness T1 [mm] at the end of the laminated glass (measurement point E). In this example, the measurement point E was the center point of one side of the outer periphery of the laminated glass, and the measurement point I was a position 50 mm inward from the measurement point E toward the center of the laminated glass. The results are shown as thickness difference in FIG. 3, with the laminated glass 1A as Example 1 and the laminated glass 1B as Example 2. <Evaluation> (exterior) The appearance of the laminated glass 1A and the laminated glass 1B was visually evaluated according to the following criteria. ◯ (Good): No air remaining or bubbles were observed in the area 3 mm inside from the edge of the laminated glass. △(Fair): 20mm in the area 3mm inside from the edge of the laminated glass 2 Less than 10% air and foaming are observed. × (Poor): 20 mm in the area 3 mm inside from the edge of the laminated glass 2 At least one of the above air residue and bubbles is observed. (Durability rating) The laminated glass 1A and the laminated glass 1B were placed in a thermohygrostat at 60°C and 95%RH for 500 hours. Moisture was allowed to penetrate the intermediate adhesive layer, creating an environment in which peeling due to residual stress is likely to occur, and the presence or absence of peeling was visually evaluated. 2 If peeling of 20mm or more is confirmed, mark it as ×. 2 When peeling of less than 100% was observed, it was rated as △, and when peeling was not observed, it was rated as ◯.

[0080] The evaluation results are shown in Figure 3 along with w, ti, ts, whether Formula 1 is satisfied (if satisfied, it is marked as "○"; if not, it is marked as "×"), whether Formula 2 is satisfied (if satisfied, it is marked as "○"; if not, it is marked as "×"), and the manufacturing method (A: vacuum heat bonding only, B: vacuum heat bonding + pressure heat bonding). [Examples 3-16] In Examples 1 and 2, (1) the shape of the SPD light control film 3 was changed to w as shown in Figure 3 while keeping the material the same, (2) the total thickness ti of the intermediate adhesive layers 2A and 2B was changed to that shown in Figure 3 while keeping the material the same, and (3) manufacturing method A or B was selected as shown in Figure 3 to produce laminated glass of Examples 3 to 16, and evaluations were performed in the same manner as above. The measurement results are shown in Figure 3. In Examples 7, 8, 23, and 24, which are comparative examples, air remained, and the appearance evaluation was "x". [Examples 17-32] In Examples 1 and 2, LCF-1103DHA30 (product name, Hitachi Chemical Co., Ltd., SPD light control film, 0.28 mm thick) was used as the light control film 3 instead of LCF-1103DHA90 (product name, Hitachi Chemical Co., Ltd.), (1) the shape of the light control film 3 was changed to w as shown in Figure 3, (2) the intermediate adhesive layers 2A and 2B were made of the same material but the total thickness ti was changed as shown in Figure 3, and (3) A or B was selected as the manufacturing method as shown in Figure 3 to produce the laminated glass of Examples 17 to 22, and the same evaluation was performed as above. The measurement results are shown in Figure 3. [Examples 33-42] In Examples 1 and 2, the light control film 3 was replaced with MIYO film (product name, manufactured by Kyushu Nanotec Optics, PDLC film, 0.12 mm thick) instead of LCF-1103DHA90 (product name, manufactured by Hitachi Chemical Co., Ltd.), (1) the shape of the light control film 3 was changed to w as shown in Figure 3, (2) the intermediate adhesive layers 2A and 2B were made of the same material but the total thickness ti was changed as shown in Figure 3, and (3) the manufacturing method A or B was selected as shown in Figure 3, and the laminated glasses of Examples 23 to 32 were produced and evaluated in the same manner as above. The evaluation results are shown in Figure 3. FIG. 3 shows that if requirements (i-1) and (i-3) are met and the relationship between w, ti, and ts satisfies formula 1 (requirement (i-2)), that is, if all requirements (i-1) to (i-3) are met, it is possible to protect the edges of the light control film without impairing the appearance, and to obtain laminated glass with improved productivity.

[0081] Although the present invention has been described above based on the embodiments and examples, the present invention is not limited to the above embodiments and examples, and various modifications are possible within the scope of the claims.

[0082] This application claims priority from basic application No. 2019-038676, filed on March 4, 2019, with the Japan Patent Office, the entire contents of which are incorporated herein by reference. [Explanation of symbols]

[0083] 10A Laminated Glass 1A, 1B Glass plate 2A,2B Intermediate adhesive layer 3. Light control film.

Claims

1. A pair of glass plates facing each other; a pair of intermediate adhesive layers located between the pair of glass plates and in contact with the pair of glass plates, respectively; A laminated glass having a light control film capable of switching visible light transmittance, the light control film being located between the pair of intermediate adhesive layers, The laminated glass has a substantially polygonal shape in a plan view, and at least one side of the outer periphery of the laminated glass satisfies the following requirements (i-1) to (i-3). (i-1) The outer periphery of the light control film is located a distance w [mm] inside from the outer periphery of the laminated glass in a plan view, (i-2) When the thickness of the light control film is ts [mm] and the total thickness of the pair of intermediate adhesive layers is ti [mm], The w is 5 mm or more and 20 mm or less, The ts is 0.12 mm or more and 0.35 mm or less, The ti is 0.8 mm or more and 1.6 mm or less, The w, ti, and ts satisfy the following formula 1, 0<w / ti<7 / ts Formula 1 (i-3) The pair of intermediate adhesive layers contact each other in a region from the outer periphery of the laminated glass to the outer periphery of the light control film.

2. The laminated glass according to claim 1, wherein at least two sides of the outer periphery of the laminated glass satisfy the requirements (i-1) to (i-3).

3. The laminated glass according to claim 2, wherein the requirements (i-1) to (i-3) are satisfied over the entire outer periphery of the laminated glass.

4. The laminated glass according to any one of claims 1 to 3, wherein an edge of the laminated glass that satisfies the requirements (i-1) to (i-3) in an outer periphery thereof further satisfies the following requirement (i-4): (i-4) The w, ti, and ts satisfy the following formula 2. 0<w / ti<4.5 / ts Formula 2

5. The laminated glass according to any one of claims 1 to 4, wherein the laminated glass has a substantially quadrilateral shape in a plan view.

6. The laminated glass according to claim 5, wherein the laminated glass has a substantially quadrilateral shape in a plan view, and the width w is 10 mm or less on at least one side that satisfies the requirements (i-1) to (i-3).

7. 7. The laminated glass according to claim 1, wherein a material of the intermediate adhesive layer comprises at least one selected from the group consisting of a polyvinyl butyral resin, an ethylene-vinyl acetate copolymer resin, a polyurethane resin, an ionomer resin, and a cycloolefin polymer.

8. The intermediate adhesive layer has a minimum storage modulus of 2.0×10 in a temperature range of 90 to 120° C. in dynamic viscoelasticity measurement at a measurement frequency of 10 Hz. 6 The laminated glass according to any one of claims 1 to 7, wherein the viscosity is 0.05 Pa or less.

9. The laminated glass according to any one of claims 1 to 8, wherein T2 - T1 is 0.28 mm or less, where T1 is a total thickness of the laminated glass at an end of the laminated glass and T2 is a total thickness of the laminated glass 50 mm inward from the end.

10. The laminated glass according to any one of claims 1 to 9, which does not have a dark-colored shielding layer on its peripheral edge.

11. The laminated glass according to any one of claims 1 to 10, wherein the light management film is a suspended particle device, a polymer dispersed liquid crystal, a polymer network liquid crystal, a guest host liquid crystal, a VA type liquid crystal, a TN type liquid crystal, a photochromic, an electrochromic, or an electrokinetic.

12. The laminated glass according to any one of claims 1 to 11, wherein the light control film has a thickness ts of 0.28 mm or less.

13. The laminated glass according to any one of claims 1 to 12, wherein a ratio of an area of ​​the light control film to an area of ​​the laminated glass in a plan view is 0.7 or more.

14. The laminated glass according to any one of claims 1 to 13, wherein the laminated glass is attached to a vehicle, and the thickness of the glass plate located on the inner side of the pair of glass plates is thinner than the thickness of the glass plate located on the outer side of the vehicle.

15. The glass sheet located on the inside of the vehicle has a composition containing iron of Fe as a total iron amount based on oxide. 2 O 3 The laminated glass according to claim 14, wherein the total amount of the SiO2-containing gas is 0.4% by mass or more in terms of total mass.

16. 16. The laminated glass according to claim 14, wherein the thickness of the intermediate adhesive layer located on the vehicle inner side of the pair of intermediate adhesive layers is thinner than the thickness of the intermediate adhesive layer located on the vehicle outer side.

Citation Information

Patent Citations

  • Wind shild glass having inside plate of chemically strengthened silicate glass

    JP1979100415A

  • Transformer protecting ratio differential operation relay

    JP1981066128A

  • Transparent laminated glass and its use

    JP2013525235A

  • Heat-shielding laminated glass for automobile

    JP2017122025A

  • Laminated glass

    JP2017186179A